Model Pengelolaan Badan Usaha Milik Desa (BUMDes) Dalam Membangun Perekonomian Desa (Studi Kasus Desa Masalima) - Ryan Marala; Hendro Wibowo; Rachmat Rizky Kurniawan (JURNAL EKONOMI DAN PERBANKAN SYARIAH, 2018)
The author conducts research Model Management of Village Owned Enterprises (BUMDes) in Building Village Economy. The goal is to know and recognize the attraction and potential of Masalima Village to be optimized and know how to set up Village Owned Enterprises (BUMDes) as well as to know the Model Management of BUMDes in improving the economy of Masalima Village community. The research method used is the type of qualitative research with descriptive description is a study that aims to obtain a picture to understand and explain the model management of Village Owned Enterprises (BUMDes) in Developing the Village Economy. In this study the authors analyze what potentials can be developed in Masalima Village so that it can be developed and processed through the Village Owned Enterprises (BUMDes).